Obesity in Postmenopausal Breast Cancer Patients: It Is Time to Improve Actions for a Healthier Lifestyle. The Results of a Comparison Between Two Italian Regions With Different “Presumed” Lifestyles - Cortesi, Laura; Galli, Giulia Raffaella; Domati, Federica; Conte, Luana; Manca, Luigi; Berio, Maria Antonietta; Toss, Angela; Iannone, Anna; Federico, Massimo (Frontiers in Oncology, 2021)
Background. Adult body fatness is a convincing risk factor for postmenopausal breast cancer. With the aim to compare the different BC features in Northern and Southern Italy, we investigated the relationship between BMI and BC characteristic in two groups of patients referred in the Modena and Lecce breast units. Materials and Methods. A retrospective analysis of a continuous series of BC patients referred to the Città di Lecce Hospital and the Modena Cancer Center, from January 2019 to December 2020 was performed. We identified four groups of BMI at BC diagnosis: underweight, BMI<18.5 kg/m2; normal weight, BMI 18.5-24.9 kg/m2; overweight, BMI 25.0 -29.9 kg/m2; obese, BMI≥30.0 kg/m2. BC characteristics and clinical outcomes were analyzed by the Kolmogorov–Smirnov test and Mann Whitney test; categorical data were compared using Pearson’s chi- square test and dicotomic data were compared by odds ratio. Results. Nine hundred seventy-seven BC patients were included in the analysis. Overall, 470 were from Modena and 507 from Lecce. No differences were observed in the mean age of BC patients of Modena (61,42) and Lecce (62,08). No statistical differences between the two populations were shown in terms of tumor characteristics and pathological stage. Conversely, a statistical difference of BMI between the BC patients coming from Modena and Lecce (25.87 and 27.81, respectively; P= 0.000001) was found. BC patients diagnosed in Lecce at age ≥70 years had higher median BMI compared to the ones from Modena (P = 0.000002). The increased BMI in this aged population was also associated to larger tumor size (P=0.040). Conclusion. The rate of overweight and obesity was higher in BC women living in Southern Italy, despite the presumed nutrition according to the so-called ‘Mediterranean type’ dietary pattern. Unexpectedly, an increased BMI rate and a relationship with larger tumor size was found in Southern BC patients aged ≥70 years. Our findings strongly support the need for promoting a healthier lifestyle model in Italy, with the aim of reducing the rate of the obesity and, consequently, the increased risk of BC.